Analysis of the Suitability of Quick-Type Hand Tractors and Power Requirements for Wetland Cultivation in Lima Puluh Kota Regency, West Sumatra Province - Zulnadi; Irwan A; Sri Lismawati (Postgraduate, University of Mataram, 2026)
In Lima Puluh Kota Regency, there are many models and types of hand tractors used by farmers to cultivate rice fields. However, it is necessary to identify which models and types of hand tractors are most suitable for use on agricultural land. The aim of this study was to determine the suitability of the hand tractors used, covering the technological (technoware), user (humanware), management (organoware) and information delivery (infoware) aspects. This study was conducted in 11 sub-districts in Lima Puluh Kota Regency. The research locations were selected using a purposive sampling method. The equipment used in this study comprised Quick-type hand tractors fitted with Kama (4.5 hp), Ratna (6.5 hp) and Yanmar (8.5 hp) engines. The first stage of data collection involved conducting a survey of relevant agencies. The second stage was a field survey. The third stage involved direct performance testing carried out under various rice field conditions. Each sub-district was represented by two farmers’ groups owning Quick hand tractors with three types of engines: Kama, Ratna and Yanmar. The research results showed that the highest working capacity for rice field cultivation using a rotary plough was found in Payakumbuh sub-district with the Yanmar hand-operated tractor, at 0.075 ha/hour. Meanwhile, the lowest effective working capacity was found in Koto Tinggi sub-district with the Kama hand-operated tractor, at 0.022 ha/hour.